The Humanistic Approach in Adolescent Counseling - Ria, Ria (PT. Anagata Sembagi Education, 2025)
Abstract The humanistic approach in adolescent counseling offers a paradigm that emphasizes the positive potential of individuals, empathy, and authentic therapeutic relationships. This article explores the effectiveness of the humanistic approach in helping adolescents overcome various psychological challenges such as anxiety, academic stress, and identity search. This research was conducted using a qualitative approach through literature studies and case observations in several high schools in Indonesia. The results of the study indicate that this approach is able to create a safe, supportive, and empowering counseling environment. Key factors for its success lie in unconditional acceptance, the presence of an empathetic counselor, and providing space for adolescents to explore their own feelings and thoughts. The humanistic approach is also considered more flexible and in accordance with the needs of adolescent psychosocial development. This article recommends the integration of the humanistic approach in school guidance and counseling programs more broadly as a strategy to strengthen adolescent mental health in the modern era full of challenges.